Simultaneous Analysis of Four Bioactive Compounds in Migan Granules Using Internal Addition Standard Method in Gas Chromatography - Xu1, Guofang; Li1, Xiaohua; Liu1, Ping; Li1, Guanghui; Hua1, Zhihui; Li2, Xiaosu (Asian Journal of Chemistry, 2014)
A simple and reliable gas chromatography method with flame ionization detector was developed for the separation and quantification of four bioactive essential compounds including deoxyschizandrin, schizandrin B, schisandrol A and imperatorin in a traditional Chinese medicine preparation (TCMP), Migan granules. The analytes were distilled with steam distillation. The separation was achieved on an HP-5 phenyl methyl siloxane capillary column (30 m × 0.32 mm, i.d. × 0.50 μm) with temperature programmed. The LODs and LOQs of the four analytes were less than 2.10 and 6.93 μg/mL, respectively. The intra-day and inter-day coefficients of variation were less than 4.3 % (RSD) and the recoveries were in the range of 91.4-99.3 % for all four analytes. The validated method was successfully applied to simultaneously determine the four essential compounds in Migan granules.